"Sea anemone" symptom in diagnosis of fallopian tubes function - В. В. Дощечкин (Publishing House TRILIST, 2017)
The article presents the method of ultrasonographic diagnosis of fallopian tubes function by the "Sea Anemone Symptom". Objective: to study the function of patent uterine tubes in women among the couples with unexplained subfertility. Design: prospective cross-sectional study. Patients, Methods, Settings: 43 subfertile women were included into the study group. Non-contrast transvaginal sonography was carried out in all patients by the technique of mobile hydro-acoustic window (TVS+MHAW). The new "Sea Anemone Symptom" test (SAS-test) was performed for the ultrasonographic assessment of the function of fallopian tubes. In all women uterine tubes patency was confirmed by laparoscopic chromoperfusion, retro- and prospectively. The study was conducted in the Odesa center for reproductive medicine "Remedi" in the period from July 16 to December 16, 2016. Results and discussion: 4 main sonographic phenotypes of fallopian tube funnels and associated various difficult-to-visualized pathological pelvic subjects were identified. SAS-test positive sonographic assessment confirming the functionality of one or both uterine tubes' funnel was obtained in 30 (69.75%) of 43 women. In 10 (23.25%) negative results of SAStest served as a ground for suspicion of altered fimbriae of fallopian tubes. In 3 (7.0%) cases test results appeared doubtful. Diagnostic accuracy of SAS-test was evaluated based on the laparoscopic findings. Pathology of fallopian tubes was confirmed laparoscopically in 8 women with positive, 9 with negative and 2 women with questionable results of SAS-test. Conclusion: the SAS-test can be used in the management of couples with unexplained infertility, when deciding on the advisability of laparoscopy. The TVS+MHAW method with its advantages in accuracy, non-invasiveness and safety profile, can serve as the first-line diagnostics of hard-to-see pelvic subjects associated with fimbriae of fallopian tube in subfertile female.